Inflammatory response of cultured macrophages in treatment-naive patients with systemic sclerosis - E. V. Gerasimova; A. I. Bogatyreva; T. V. Kirichenko; T. V. Popkova; R. U. Shayakhmetova; L. P. Ananyeva; Yu. V. Markina; A. M. Markin; A. N. Orekhov (Научно-практическая ревматология)
Background. Сhronic inflammation is one of the main factors in the progression of systemic sclerosis (SSc). Macrophages activated via a proinflammatory pathway can be considered as major participants in the maintaining of system chronic lowgrade inflammation.The aim of this study was to evaluate the inflammatory response and of macrophages in patients with systemic sclerosis to reveal the most significant inflammatory mediators in pathogenesis of this disease.Materials and methods. The study included 34 treatment-naive SSc patients and 17 controls. Macrophages were obtained by culturing peripheral blood monocytes. The macrophage response was analyzed by deviations in the parameters of basal, lipopolysaccharide (LPS) stimulated, and restimulated secretion of the tumor necrosis factor α (TNF-α), interleukin (IL) 1β, C-C motif ligand 2 (CCL2), and IL-8 by cultured macrophages in SSc patients compared to the control group. The levels of basal and LPS-stimulated secretion were assessed on day 1. The second LPS stimulation was performed on day 7 to assess the cell response to repeated stimulation (restimulated secretion) after the first stimulation to characterize the resistance of the macrophage immune response. Cell resistance (tolerance) was calculated as the ratio of secretion during repeated stimulation to LPS-stimulated secretion. Concentrations of TNF-α, IL-1β, CCL2, and IL-8 cytokines in the culture fluid were determined out using an enzyme-linked immunosorbent assay.Results. Basal and restimulated secretion of all studied cytokines was significantly higher in the SSc group compared to the control group; LPS-stimulated secretion was statistically significantly higher in the SSс group only for IL-1β. Impaired resistance of the immune tolerance of macrophages to CCL2 was detected in 50% of treatment-naive SSc patients.Conclusions. The results of the study demonstrate a pro-inflammatory response of macrophages with increased levels of basal and restimulated secretion of TNF-α, IL-1β, CCL2 and IL-8, as well as impaired tolerance of the immune response of macrophages in treatment-naive SSc patients in relation to the secretion of CCL2. These data indicate the active participation of CCL2 in the development of chronic inflammation in SSc that can be considered as a target for the development of new therapeutic approaches for SSc.